RETRACTED: Metformin Protects From Rotenone–Induced Nigrostriatal Neuronal Death in Adult Mice by Activating AMPK-FOXO3 Signaling and Mitigation of Angiogenesis - El-Ghaiesh, Sabah H.; Bahr, Hoda I.; Ibrahiem, Afaf T.; Ghorab, Doaa; Alomar, Suliman Y.; Farag, Noha E.; Zaitone, Sawsan A. (Frontiers in Molecular Neuroscience, 2020)
Parkinson’s disease (PD) is a neurodegenerative disease that affects substantia nigra dopamine neurons. Many studies documented the role of oxidative stress and angiogenesis in pathogenesis of PD. Metformin (MTF) is an antidiabetic medication and AMPK regulator that showed antioxidant and antiangiogenic properties in many disorders. The aim of this study is to investigate the neuroprotective effect of MTF in a mice model of rotenone prompted PD with a highlight on its influence on AMP-activated protein kinase (AMPK)/forkhead box transcription factor O3 (FOXO3) pathway and striatal angiogenesis . In the running study, PD was induced in mice using repeated doses of rotenone and concomitantly treated with MTF 100 or 200 mg/kg/day for 18 days. Rotarod and pole tests were used to examine animals' motor functionality. After that, animals were sacrificed, and brains were isolated and processed for immunohistochemical investigations or biochemical analyses. Oxidant stress and angiogenic markers were measured including reduced glutathione, malondialdehyde, Nrf2, hemoxygenase-1, thioredoxin, AMPK, FOXO3 and vascular endothelial growth factor (VEGF). Results indicated that MTF improved animals’ motor function, improved striatal glutathione, Nrf2, hemoxygenase-1 and thioredoxin. Furthermore, MTF upregulated AMPK-FOXO3 proteins and reduced VEGF and cleaved caspase 3 along with diminished DNA fragmentation. MTF also increased tyrosine hydroxylase immunostaining in the substantia nigra neurons and in striatal nerve terminals. This study is the first to highlight that the neuroprotective role of MTF is mediated through activation of AMPK-FOXO3 signaling and inhibition of the proangiogenesic factor, VEGF. Further studies are warranted to confirm this mechanism in other models of PD and neurodegenerative diseases.